Addressing Intimate Partner Violence Against Men through Community-Based Interventions and Social Worker Services - Rowlands, Emmanuel (Journal of Posthumanism, 2025)
Despite growing evidence of male victimization in intimate relationships, South Africa, like many other countries, lacks evidence-based guidance on how to effectively intervene and support male victims of abuse. This gap in research, policy, and practice has significant implications, as male victimization continues to increase in pervasive and often underreported forms. The absence of targeted interventions for male victims not only exacerbates their suffering but also perpetuates harmful gender stereotypes that dismiss men’s experiences of intimate partner violence (IPV). This study examines the need for community-based intervention and social workers services as unique approaches to addressing IPV against men. A qualitative method was employed to explore the perspectives of workable interventions among 25 Africa men living in Johannesburg South Africa who are survivors of IPV. Additionally, the expertise perspectives of five professionals from the Police and health care working with survivors of IPV were sought. The results indicates that despites the common assumptions that men don’t talk, male IPV victims in South Africa were significantly likely to seek and use the services of social workers as formal support while in abusive relationships. The findings also suggest that community-based interventions will contribute significantly to the reduction of IPV against men. These findings underscore the importance of community-based programs that advances gender equality discusses and promote healthy masculinity that is open to vulnerability as a way of reshaping societal perceptions of IPV against men to create a judgment-free environment where male victims feel empowered to seek help.